Understanding Market Behavior on Corn Commodity: Phenomenon at Year End - Darma, Surya; Hakim, Yundi Permadi; A, Erwin Kurniawan; Darma, Dio Caisar; Suparjo, Suparjo (Asian Journal of Agriculture and Rural Development, 2022)
The cause of market failure is the lack of synchronization between supply and demand, or vice versa. Initially, corn was considered as a substitute and a complementary commodity for food, but now it has turned into a basic need for people in Indonesia, especially when they celebrate the new year. The main aim of this study is to examine the interaction between the demand side and the supply side. The study was carried out by inviting 9,850 respondents in Samarinda City to be surveyed regarding interest, tradition, taste, price, opportunity, profit, production cost, and distribution. Empirical testing was used to interpret the data, including correlation, reliability, and validity. Constructive validity was found in the market behavior function, where the indicators of consumer demand (p < 0.01) and produce supply (p < 0.01) have a significant effect. Also highlighted were production cost and distribution, both of which have a positive channel and are closely related to the other six indicators. The consistent performance of production cost and distribution supported further evidence providing stability of measurement results. Additionally, tradition and opportunity also produced high coefficients in the reliability test. We can further examine empirical results by including other dimensions, such as social, psychological and individual factors. In addition, diagnostic transformations need to be highlighted where market trends can change along with the growth of other commodities.